Influence of root canal sealer on the radiographic appearance of filling voids in maxillary single-rooted teeth - Augusto Bodanezi; Etiene Andrade Munhoz; Ana Lúcia Álvares Capelozza; Norberti Bernardineli; Ivaldo Gomes de Moraes; Roberto Brandão Garcia; Clovis Monteiro Bramante (University of São Paulo, 2012)
OBJECTIVE: This study compared the influence of three epoxy resin-based sealers with distinct radiopacities on the observers' ability to detect root canal filling voids during radiographic analysis. MATERIAL AND METHODS: The root canals of 48 extracted maxillary canines were prepared and divided into three groups. Each group was laterally condensed with one sealer (AH Plus®, Acroseal® or a non-radiopaque sealer), and a longitudinal void was simulated in half of the specimens from each group (n=8). Buccolingual radiographs were obtained and randomly interpreted for voids by a radiologist and an endodontist in a blinded fashion. Teeth were cut and inspected under a microscope to confirm the position of void. Differences in sensitivity and specificity between groups and examiners were compared using the Fisher's Exact and McNemar tests, respectively (α=0.05). RESULTS: Significantly lower sensitivity levels (p<0.05) were observed in the coronal portion of fillings performed with both radiopaque sealers. Specificity values for Acroseal® were significantly higher (p<0.05) in the coronal and apical portions of fillings. CONCLUSIONS: The type of root canal sealer can affect the observers' ability to detect root canal filling voids during radiographic analysis of upper single-rooted teeth.